One Little Lie - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2020)
"Book one in a gripping new series from USA TODAY bestselling romantic suspense author Colleen Coble"--
"USA Today bestselling author"--Dust jacket.
Keywords: Sheriffs -- Fiction; Alabama -- Fiction; Romantic suspense fiction; Christian fiction